Coordinated and cohesive movement of two small conspecific fish induced by eliciting a simultaneous optomotor response. - Haruka Imada; Masahito Hoki; Yuji Suehiro; Teruhiro Okuyama; Daisuke Kurabayashi; Atsuko Shimada; Kiyoshi Naruse; Hiroyuki Takeda; Takeo Kubo; Hideaki Takeuchi (PLoS ONE, 2010)
BACKGROUND: In animal groups such as herds, schools, and flocks, a certain distance is maintained between adjacent individuals, allowing them to move as a cohesive unit. Proximate causations of the cohesive and coordinated movement under dynamic conditions, however, have been poorly understood. METHODOLOGY/PRINCIPAL FINDINGS: We established a novel and simple behavioral assay using pairs of small fish (medaka and dwarf pufferfish) by eliciting a simultaneous optomotor response (OMR). We demonstrated that two homospecific fish began to move cohesively and maintained a distance of 2 to 4 cm between them when an OMR was elicited simultaneously in the fish. The coordinated and cohesive movement was not exhibited under a static condition. During the cohesive movement, the relative position of the two fish was not stable. Furthermore, adult medaka exhibited the cohesive movement but larvae did not, despite the fact that an OMR could be elicited in larvae, indicating that this ability to coordinate movement develops during maturation. The cohesive movement was detected in homospecific pairs irrespective of body-color, sex, or albino mutation, but was not detected between heterospecific pairs, suggesting that coordinated movement is based on a conspecific interaction. CONCLUSIONS/SIGNIFICANCE: Our findings demonstrate that coordinated behavior between a pair of animals was elicited by a simultaneous OMR in two small fish. This is the first report to demonstrate induction of a schooling-like movement in a pair of fish by an OMR and to investigate the effect of age, sex, body color, and species on coordination between animals under a dynamic condition.